2004
DOI: 10.1074/jbc.m314228200
|View full text |Cite
|
Sign up to set email alerts
|

Hif1 Is a Component of Yeast Histone Acetyltransferase B, a Complex Mainly Localized in the Nucleus

Abstract: Hat1 is the catalytic subunit of the only type B histone acetyltransferase known (HAT-B). The enzyme specifically acetylates lysine 12, and to a lesser extent lysine 5, of free, non-chromatin-bound histone H4. The complex is usually isolated with cytosolic fractions and is thought to be involved in chromatin assembly. The Saccharomyces cerevisiae HAT-B complex also contains Hat2, a protein stimulating Hat1 catalytic activity. We have now identified by two-hybrid experiments Hif1 as both a Hat1-and a histone H4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
159
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(171 citation statements)
references
References 64 publications
10
159
1
1
Order By: Relevance
“…The purified protein was crystallized in complex with AcCoA and histone H4 peptide (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. After an initial screen, we used the alkylated enzyme to improve crystal quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified protein was crystallized in complex with AcCoA and histone H4 peptide (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. After an initial screen, we used the alkylated enzyme to improve crystal quality.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies showed that HAT1 is predominantly localized in the nucleus (3)(4)(5)(6) where it forms a trimeric complex with HAT2 and the histone chaperone HIF1. HIF1 is detected exclusively in the nucleus and accompanies newly modified H3-H4 tetramers to facilitate their incorporation into nascent chromatin during DNA synthesis.…”
mentioning
confidence: 99%
“…It is interesting to note that HAT1, which acetylates Lys-5 and Lys-12 on newly synthesized soluble histone H4, was originally termed the cytoplasmic HAT (31, 32), although it is now known to be mostly nuclear (33). However, it is still a matter of debate as to where the acetylation of soluble histones occurs, and there is evidence that H4 is acetylated in the cytoplasm (34).…”
Section: Asf1 Is Likely To Present the Newly Synthesized Freementioning
confidence: 99%
“…The protein Hif1, similar to Hat2, is a histone H3-H4 specific chaperone and was initially identified as a component of the HAT-B complex where it has been hypothesized to be responsible for recruiting histones H3-H4 to HAT-B. Deletion experiments have shown that the loss of Hif1 in combination with K9R and K14R mutations in H3 is comparable to deletion of Hat1, which results in defects of telomeric silencing and DNA double-stranded break repair (19). The association of the histone chaperone Hif1 with HAT-B was the first direct evidence implicating a role for Hat1 in the chromatin assembly process (17).…”
mentioning
confidence: 99%